DAB-induced changes in NMR relaxation times, water and iron content of rat tissue. - Ling, C. R. (Nature Publishing Group, 1980)
T1 relaxation values of rat liver and spleen tissue have been measured over a 6-month period whilst feeding with p-dimethyl-aminoazobenzene (DAB). Measurements of tissue water and iron content have also been made. A small rise in liver T1 value during the early stages of DAB feeding, from a control value of 296 +/- 12 ms to 318 +/- 12 ms after 3 weeks, probably reflected toxic reaction to the diet rather than preneoplastic changes. Spleen T1 value showed a considerable decrease over this same period, from a mean control value of 505 +/- 14 ms to 394 +/- 21 ms after 3 weeks on the diet. The possible origins of this change are discussed.